MOTIVASI CALON LEGISLATIF (CALEG) UNTUK MENCALONKAN DIRI PADA PEMILU DITINJAU DARI JENIS KELAMIN - Ismiati Ismiati; Siti Hajar Sri Hidayati (Pusat Studi Wanita UIN Ar-Raniry, 2017)
Gender equality is the most important thing to prevent discrimination in the community. One way to achieve gender equality is by providing access to women to influence political policy, such as participating in politics, becoming legislative candidates. The low percentage of women legislatures, especially in Aceh shows that women are still not actively participating in politics. The cause factor is low motivation. This study aims to see the motivation of legislative candidates in terms of sex. The result of the research shows that there is a difference of motivation between male and female legislative candidates. The motivation of male candidates is more dominated by need for power which is a need to influence and control others. In contrast to female legislative candidates who are more dominated by need for affiliation which is a need to develop and maintain interpersonal relationships with others.